Avaliação de parâmetros de bem-estar animal em frangos de corte nas etapas de pré-abate e abate. - Paula, Nayara Martins de (Universidade Federal do Tocantins, 2023)
The curricular internship was realized from 18 April 2016 to 30 July 2016 in poultry slaughterhouse industrial complex Aroldo Silva Amorim, Bonasa S.A. group located in the northern state of Tocantins, located about 8 kilometers from city Aguiarnópolis TO, with the percent of slaughter capacity and sixty thousand (160,000) poultry/day. Under the supervision of the veterinary Fernanda A. Alcântara Conceição coordinator of quality control and inspector of the Federal Inspection Service, Daniella Dandi F. Sousa. The stage was carried out under the leading of Dr. Catia Maria de Oliveira Lobo, over forty-nine days totaling three hundred ninety-two hours. During this period was carried out monitoring of all meat production stages of poultry and analysis of some parameters related to animal welfare and humane slaughter at poultry slaughterhouse based on the protocol conducted by WSPA where they are defined critical control points and the control point related to animal welfare and humane slaughter in the pre-slaughter and slaughter aimed to preserve the ethical quality and the sanitary quality of marketed products.